Classical thiazole orange and its regioisomer as fluorogenic probes for nucleolar RNA imaging in living cells. Issue 3 (5th January 2023) - He, Mengmeng; Sato, Yusuke; Nishizawa, Seiichi
Abstract : Thiazole orange (TO) performs as a promising fluorogenic dye for nucleolar RNA imaging in living cells. More interestingly, 2TO, a regioisomer of TO, performs much better and has superior selectivity for RNA in both solution and living cells. Abstract : In contrast to well-established DNA-selective dyes for live cell imaging, RNA-selective dyes have been less developed owing to the challenges of making small molecules have RNA selectivity over DNA. Two kinds of dyes are now commercially available for nucleolar RNA imaging in cells, but these two dyes do not apply to living cells and have limited use in fixed and permeabilized cells. Herein, we report on thiazole orange (TO), a well-known nucleic acid stain, as a promising fluorogenic dye for nucleolar RNA imaging in living cells. TO shows clear response selectivity for RNA over DNA with a significant light-up property upon binding to RNA ( λ em = 532 nm, I / I 0 = 580-fold, and Φ bound / Φ free = 380) and is even applicable to wash-free imaging of living cells. More interestingly, 2TO, a regioisomer of TO in which the benzothiazole unit is connected to position 2 in the quinoline ring, performs much better ( λ em = 532 nm, I / I 0 = 430-fold, Φ bound / Φ free = 1200), having superior selectivity for RNA in both solution and living cells. The comparison with TO derivatives carrying different substituents at N1 of the quinoline ring reveals that the slight change in the TO framework significantly affects RNA selectivity, photostability and membrane permeability.